PENGEMBANGAN MODUL PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL GUNA PEMBENTUKAN KARAKTER POSITIF SISWA KELAS III SD NEGERI 01 PURWOSARI - Jaziroh; Dewi Apriani; Basukiyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The character formation of elementary school students is a critical issue in education, especially in rural areas where the influence of local culture can play a vital role. This study aims to develop a character education module based on local wisdom to foster positive character traits among third-grade students at SD Negeri 01 Purwosari. Using the Research and Development (R&D) method with the 4D model Define, Design, and Develop the research focused on designing and validating a character education module that integrates local traditions, values, and folklore. Data were obtained through observations, interviews, expert validation, and limited-scale trials. The findings revealed that the character education module based on local wisdom is valid, practical, and effective in supporting students' character development. Students demonstrated significant improvement in character indicators such as religious values, honesty, empathy, politeness, and cooperation, with an N-gain score of 0,59 (moderate category). The integration of local cultural elements into the learning process not only enhanced character outcomes but also strengthened students’ cultural identity. This research concludes that the developed module has strong potential to be implemented more widely in character education practices.